Instrumentalno merjenje ohlapnosti kolena v antero-posteriorni smeri - Jeromel, Miran (Zdravniški vestnik, 2004)
Background. A magnitude of clinical tests (like Lachman test) are used to diagnose antero posterior knee instability. They are easy to preform but they are very suhjective. An experienced practitioner is often required. An alternative to standard clinical tests is the usage of arthrometer which requires a cooperative patient (maximal relaxation of thigh muscles). The aimsof this study were to assess the antero posterior laxity of both knees in the normal population (population without prior injury to the knee) and to determine knee laxity in terms of total relaxation (usage of miorelaxant) under general anaesthesia. We compared the difference between the left and right knee of the same individual and the influence of ageing and gender on knee laxity. We also studied the influences of diabetes and long-term corticosteroid therapy. We wanted to prove the following theories: complete relaxation of thigh muscles has an effect on measurement of knee laxity; the individual without prior knee injury has no statistically side to side difference; the laxity increases with age; women have grater ligamentous laxity than men. Laxity increases as the result of diabetes and also as a result o f longterm corticosteroid therapy. Methods. Arthrometer KT 1000/STM (Medmetric) was used in our survey. We analysed 90 individuals (aged 18-81) who haven't had knee injuries in the past. Among them were 45 (50%) men and 45(50%) women. 8 (8.9%) of them were diabetics and 4 (4.4%) of them received long-term corticosteroid therapy. We assessed the antero posterior laxity of both knees of an individual under the effect of general anaesthetic. Each measurement was repeated thrice. The same procedure was used to determinate antero posterior laxity without the usage of anaesthetic. (Abstract truncated at 2000 characters).
Keywords: Adrenal Cortex Hormones; Diabetes Mellitus; Diagnosis; Fizikalna preiskava; Joint Diseases; Knee Joint; Kolenski sklep; Kortikosteroidi; Mišična relaksacija; Muscle Relaxation; Physical Examination; Sex Factors; Sklep, bolezni; Sladkorna bolezen; Spolni faktorji; Therapeutic Use